(Professional pressures and their relation to some teaching competencies of the teachers of physical education and sports in secondary education (A survey conducted on some secondary schools in Algeria - brahem, Harbash; bin Thhiba, Jagddam; Jamal, Mqrany; Hussein, Ben Zidan; Habib, Bin. Si Kadour (Arab Journal for Sciences and Research Publishing, 2015)
The purpose of this study was to know the professional pressure and its relation with some teaching competencies (planning-calendar-and implementation) for teachers of physical education and sports. The sample of research was 101 Professor of secondary school, that have been selected at random, which amounted to 93.51% of the total number of professors and researchers themselves oversaw distribution of the scales (a measure of professional pressures - Questionnaire teaching competencies) to professors of physical education and sports, and concluded that results in the latter that there is a relationship between professional teaching competencies pressures, but to varying degrees, were the most important suggestion or recommendation In this work is to push and motivate pupils by the Administration to exercise physical and sports education and its relevance to mitigate and reduce the pressure to the professor.